Activation of autophagy by α-herpesviruses in myeloid cells is mediated by cytoplasmic viral DNA through a mechanism dependent on stimulator of IFN genes. - Rasmussen, S; Horan, K; Holm, C; Stranks, A; Mettenleiter, T; Simon, A; Jensen, S; Rixon, F; He, B; Paludan, SR (2011)
Autophagy has been established as a player in host defense against viruses. The mechanisms by which the host induces autophagy during infection are diverse. In the case of HSV type 1 (HSV-1), dsRNA-dependent protein kinase is essential for induction of autophagy in fibroblasts through phosphorylation of eukaryotic initiation factor 2α (eIF2α). HSV-1 counteracts autophagy via ICP34.5, which dephosphorylates eIF2α and inhibits Beclin 1. Investigation of autophagy during HSV-1 infection has largely been conducted in permissive cells, but recent work suggests the existence of a eIF2α-independent autophagy-inducing pathway in nonpermissive cells. To clarify and further characterize the existence of a novel autophagy-inducing pathway in nonpermissive cells, we examined different HSV and cellular components in murine myeloid cells for their role in autophagy. We demonstrate that HSV-1-induced autophagy does not correlate with phosphorylation of eIF2α, is independent of functional dsRNA-dependent protein kinase, and is not antagonized by ICP34.5. Autophagy was activated independent of viral gene expression, but required viral entry. Importantly, we found that the presence of genomic DNA in the virion was essential for induction of autophagy and, conversely, that transfection of HSV-derived DNA induced microtubule-associated protein 1 L chain II formation, a marker of autophagy. This occurred through a mechanism dependent on stimulator of IFN genes, an essential component for the IFN response to intracellular DNA. Finally, we observed that HSV-1 DNA was present in the cytosol devoid of capsid material following HSV-1 infection of dendritic cells. Thus, our data suggest that HSV-1 genomic DNA induces autophagy in nonpermissive cells in a stimulator of IFN gene-dependent manner.